PENGARUH KNOWLEDGE MANAGEMENT PADA PERILAKU INVESTOR - Pradana, Mochammad Nugraha Reza (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
This study aims to analyze the effect of knowledge management on investor behaviour. This type of research is quantitative research. The population of this study is 211 investors who are registered at the Investment Gallery Unirsal University. The sample in this study amounted to 55 investors with random sampling technique. The data analysis technique used is the Structural Equation Model (SEM) with SMARTPLS version 3.0. The results showed that Knowledge Management has a significant influence on Investor Behaviour.